Development and Prospect of ChatGpt in the Medical Field - Zhong, Mingrui (Transactions on Computer Science and Intelligent Systems Research, 2024)
In the current era, there exists an uneven distribution of global medical resources, making it a crucial focal point for medical digital transformation. This paper aims to explore the application status, potential challenges, and future development prospects of ChatGPT, a large language model based on OpenAI, in the field of medicine. Given the current scarcity of global medical resources, this study analyzes existing medical use cases and examines the ethical and regulatory environment surrounding ChatGPT under the Transformer model within specialties like orthopedics and ophthalmology. The findings propose that its present advantages lie in its ability to support multiple languages while enhancing efficiency and quality of medical services. Furthermore, measures should be taken to reinforce privacy and security protocols for ChatGPT data usage while ensuring ethical considerations are met. Additionally, it is recommended that future advancements in ChatGPT focus on deepening its medical knowledge base and developing more specialized modules.